Analisis Faktor-Faktor Yang Mempengaruhi Daya Saing Usaha Mikro Kecil Dan Menengah (UMKM) Di Perkampungan Industri Kecil (PIK) Pulogadung Jakarta Timur - Euis Winarti; D Purnomo; Jaenudin Akhmad (POLITEKNIK LP3I JAKARTA, 2019)
In pushing the economy in the capital city of Jakarta is inseparable from the problem, one of the biggest problems of the people of the capital city in the economic field is the difficulty of empowering the people's economy, and the other side is the high unemployment in the capital. Efforts to overcome the problem of unemployment in the capital city is to provide their own employment. Provision of employment opportunities can be done by opening up Small and Medium Enterprises (SMEs). Small and Medium Enterprises play an important role in absorbing labor, contributing foreign exchange, and alleviating poverty. This is done because on the one hand it can create new entrepreneurs and on the other hand is the empowerment of small businesses into medium-sized businesses. The rapid growth of MSMEs in PIK Pulogadung Jakarta fosters competitiveness among MSMEs to maintain their business. The undeniable reality that Small and Medium Enterprises is the most strategic national economic sector and concerns the lives of many people, so that it becomes the backbone of the national economy. Lack of capital, low professionalism of managing human resources, limited capital and market access, and the lack of government role in supporting the competitiveness of SMEs are problems that must be sought for solutions for SMEs. The method used is multiple linear regression analysis to determine the effect of the dependent variable on independent variables. The research proves that simultaneously the independent variables (Capital, Human Resources, Product Marketing and Government Support) have a significant positive effect on the independent variables (Competitiveness). Keywords: Competitiveness, Small and Medium Enterprises, HR, Capital, Marketing, Government Support.